Position and Legal Consequences of Evidence of Old Rights That Are Not Converted and Controlled by Other Parties (Study of Decision No. 94/Pdt.G/2023/PN Amb) - Achmad Dwi Saputra; Amad Sudiro (Dinasti Research, 2024)
This research focuses on analyzing the legal position of holders of old certificates of title that have not been converted and the legal consequences of physical control of land by other parties who have land certificates. This study uses Decision No. 94/Pdt.G/2023/PN Amb as a case study to understand how courts balance the interests of disputing parties and apply agrarian law regulations in land ownership conflicts. This research was motivated by implementing the Basic Agrarian Law (UUPA) no. 5 of 1960, which requires converting Western rights such as Eigendom Verponding into rights recognized in the Indonesian legal system. This conversion process is regulated by Government Regulation (PP) no. 18 of 2021, but there are still many old rights holders who have not converted because they allow permits, the permit procedures are considered complicated and are permitted by law. Decision Case No. 94/Pdt.G/2023/PN Amb shows that the old right holder can maintain their rights if they can provide legal proof of ownership, even though another party physically controls the land. This research uses a normative juridical approach by examining statutory regulations, legal doctrine, and court decisions. The data analysis technique was carried out descriptively and qualitatively to evaluate the legal position of old rights and land certificates and their implications in agrarian disputes. Based on the analysis, physical control of land without legal proof of ownership is considered an unlawful act per Article 1365 of the Civil Code. The court in this case decided that the holder of the old right which had not been converted still had the right to the land, and the certificate obtained without a valid legal basis was declared invalid. This research highlights the importance of converting old rights to create legal certainty and prevent future land disputes. This conversion not only provides stronger legal protection for land owners but also ensures legal certainty for the next generation who inherits the land.